Automated-Combined valve oscillation testing machine for 4&6 Cylinders (International Journal of Engineering and Computer Science, 2017)
Valves in an engine have numerous functions to perform and they experience enormous stress even in normal conditions. Hence testing of valves is very important. The present work is focused towards design of combined valve oscillation testing machine to check two and four valve cylinder heads. Also four as well as six cylinder engine heads can be tested on the same machine. Conventionally, valves are tested on two different assembly lines separate for two and four valves. This approach has been adapted to save space, cost and time of testing. This concept incorporates mechanical, automation and pneumatic principles. As a result, it improves efficiency and speed of operation, reduces manpower. The aim is to elaborate the concept with the aid of designing. The concept is simple and reliable. The design calculations have been obtained and found to be suitable for the application stated above.